The Status of Early Childhood Health and Development in Kiribati : Results from a Population Wide Census - Brinkman, Sally (World Bank, Washington, DC, 2019)
Kiribati is among the first few countries in the world to have undertaken a national census of children’s early health and development. This report presents data collected for 7,194 children aged 3 to 5 years across 21 of the country’s islands. Data were collected on children’s health and development, their learning environments at home, and their early childhood education experience, which together, provide a snapshot of how children in Kiribati are developing in their early years and highlights factors that are playing an important role in influencing children’s outcomes. Overall, these results provide the country with valuable evidence to guide policy makers and service providers in their program planning and design, evaluation of interventions, and monitoring of children’s outcomes. It is hoped that in future, the country will drive repeat census collections, as only with repeat data over time will policy makers, service providers, and communities be able to understand if their work to support children is making a difference.